2019
DOI: 10.1111/edt.12529
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with traumatic dental injuries among schoolchildren in war‐torn Libya

Abstract: Background/Aims No previous epidemiological study has investigated the prevalence and associated factors of traumatic dental injuries (TDIs) among Libyan children. Such information is required for the planning and evaluation of health services. The aim of this study was to assess the prevalence of TDIs and associated factors among 12‐year‐old schoolchildren in Benghazi, Libya. Methods Data for this study were collected as part of a comprehensive, cross‐sectional survey investigating oral health status and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Several studies have demonstrated highly unmet treatment needs among school children: 70% of 6-year-olds and 42% of 12-yearolds have untreated caries (132,133). There is also a high level of unmet treatment needs related to dental trauma (134), dental fluorosis (135) and molar incisor hypo-mineralization (136).…”
Section: Libyamentioning
confidence: 99%
“…Several studies have demonstrated highly unmet treatment needs among school children: 70% of 6-year-olds and 42% of 12-yearolds have untreated caries (132,133). There is also a high level of unmet treatment needs related to dental trauma (134), dental fluorosis (135) and molar incisor hypo-mineralization (136).…”
Section: Libyamentioning
confidence: 99%
“…A recent survey of Libyan school children reported that 10.3% of 12‐years‐old suffered from TDIs, most of which were due to falling. 20 This observation emphasizes the importance of developing effective prevention programs and interventions in different settings to manage sport‐related TDIs. 21 , 22 However, it is unclear to what extent the coaches in sports centers in Benghazi, Libya, are prepared to handle emergencies caused by TDIs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been noticed that there is an increase in sports centers for children and adolescents who may become at increased risk for orofacial injuries. A recent survey of Libyan school children reported that 10.3% of 12‐years‐old suffered from TDIs, most of which were due to falling 20 . This observation emphasizes the importance of developing effective prevention programs and interventions in different settings to manage sport‐related TDIs 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Children's daily lives are affected by TDI in many ways, including their appearance, functionality, comfort, selfconfidence, and more. 5,6 Slurred speech, limited biting, and an unattractive appearance can all result from these alterations, which are more noticeable in the child's higher front teeth than his or her lower incisors. The loss of proximal and incisal connections might cause malocclusion in a short period of time.…”
Section: Introductionmentioning
confidence: 99%